GANGGUAN PSIKOGENIK DALAM DISKUSI SISWA KELAS VIII MTs NEGERI 1 KOTA TERNATE - Astitin Zulqifly; Muamar Abd. Halil (Universitas Khairun, 2021)
This research was conducted with the goal to explain the forms and factors psikogenik disturbance to the speaker stutter so can be used as input to the students and the teachers until easier to fix the mistake mentioned, and can improve the quality process of the learning for class VIII students of MTs Land 1 Ternate City, especially when a discussion in the process of learning languages Indonesia. The method used in this study is descriptive qualitative method with this technique collection of used data is observations, the interview, and the rocording. As for technique analyses data used is data reduction, data display, and conclusion drawing/verification. Based on the results of the data analyzing can be concluded that psikogenik disturbance the form of speaking stuttering in discussion of learing lenguage Indonesia for class VIII students of MTs Land 1 Ternate City. That thare are four part obtained for three days the research namely; Speaking stuttering in a halting speech, thare are 6 students tha teaches the 9 data mistake. The form of a mistakes talk stuttering in pronunciation pause for class VIII students of MTs Land 1 Ternate City, that should be pronunciation using a uill coma (,) but the speakers pronunciation using a pause point (.) and in the discourse do not need to pronunciation using pause but the speakers used, thare are 11 students tha pronunciation the 12 data mistakes. The form of a mistake talk stuttering in the speach of the repetition of the first syllable or the next word for class VIII students of MTs Land 1 Ternate City, the should pronunciation don’t frequent but because the speakers lost the idea to say what want speakersraised so the sound of the out are frequent thare are 11 students tha teaches the 18 data mistakes. The form of a mistake talk stuttering in pronunciation intonation pause for class VIII students of MTs Land 1 Ternate City, the should pronunciation words the intonation don’t long but speakers pronunciation with intonation the long thare are 7 students tha pronunciation the 7 data mistakes.